LDPE/Bi2O3 nanocomposites: Enhanced mechanical, dielectric, and optical properties - Sahin, Nazlican; Beyazay, Emre; Karabul, Yasar; Kilic, Mehmet; Esmer, Kadir; Ozdemir, Zeynep Guven (WILEY, 2024)
This study is focused on investigating the role of bismuth oxide (Bi2O3) nanoparticles to improve structural, optical, electrical, and mechanical properties of low-density polyethylene (LDPE). For this purpose, Bi2O3 nanoparticles were synthesized by using the solvothermal method and examined by transmission electron microscopes (TEM), x-ray diffraction (XRD), Fourier transformed infrared (FTIR) spectroscopy, and ultraviolet-visible (UV-Vis) light absorption methods. LDPE-based nanocomposites were prepared by changing the nanoparticle additive ratio in the composite from 0% to 2% by weight. The composites were analyzed in the context of their FTIR spectra, atomic force microscope (AFM) images, UV-Vis light absorption spectra, stress-strain curves, and energy storage abilities. While the AFM findings indicate a smoother surface for the composites, the optical band gap analysis reveals a slightly decreased direct optical band gap energy. The analyses based on dielectric spectroscopy also highlight the LDPE/0.5% n-Bi2O3 composite in terms of the best energy storage capability. Additionally, the highest Young's modulus, toughness, stress at break, and percentage of strain at break were also recorded for the LDPE/0.5% n-Bi2O3 composite. In this context, the LDPE/0.5% n-Bi2O3 composite with improved dielectric and mechanical properties can be suggested as a new promising LDPE-based nanocomposite with better properties for industrial purposes.
Keywords: AFM; Bi2O3 nanoparticles; dielectric spectroscopy; LDPE; tensile properties; NONLINEAR VISCOELASTICITY; SURFACE MODIFICATION; POLYMER MELTS; REINFORCEMENT; NANOPARTICLES; Polymer Science